Histopathological Effects of Omega-3 in Reducing Cartilage Destruction Progression in Mice with Knee Joint Osteoarthritis - Farry Farry; Yoyos Dias Ismiarto; M. Rizal Chaidir; Darmadji Ismono (Majalah Kedokteran Bandung, 2020)
rimary and secondary osteoarthritis relates to inflammatory processes and inflammatory mediators and is destructive to the articular cartilage. Omega-3 is known to be an alternative treatment for rheumatoid arthritis due to the anti-inflammatory effect. This study is an experimental study with simple random sampling using 36 Wistar mice, which were divided into an intervention group and a control group, to understand the effect of omega-3 in slowing progress cartilage destruction in knee joint with osteoarthritis. This study is performed at the Clinical Pharmacology Laboratory, Faculty of Medicine, Universitas Padjadjaran, and the Anatomical Pathology Laboratory, Faculty of Medicine, Universitas Padjadjaran/Dr. Hasan Sadikin General Hospital, in November 2018. Osteoarthritis was induced using intraarticular 1 mg monosodium iodoacetate injection to the mouse knee joint. The intervention group received oral omega-3 every day while the control group did not. Samples from the knee joint were extracted to evaluate the cartilage destruction histopathologically. Results were then analyzed using the Mann-Whitney test and a significant difference of the osteoarthritis grades was identified between the intervention group and the control group on day 7 (p=0.003), day 14 (p=0.003), and day 21 (p=0.003). In addition, a significant difference in the osteoarthritis grading changes was also found between the study group and the control group on day 7 and day 21 (p=0.004). Hence, omega-3 has the ability to slow down the histopathological cartilage destruction progress in mice with knee joint osteoarthritis.